Upaya Meningkatkan Hasil Belajar Matematika Siswa melalui Penerapan Model Problem Based Learning di Kelas VII SMP Negeri 1 Lolomatua - Yotina Ndruru (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
The aim of this research is to improve students' mathematics learning outcomes through the application of the problem based learning model. The type of implementation of this research is classroom action research (PTK) which is carried out in two cycles. The subjects of this research were all 20 students in class VII-A of SMP Negeri 1 Lolomatua and the object of this research was the students' mathematics learning outcomes. The data collection technique used is in the form of essay test questions and learning implementation observation sheets. Next, analysis is carried out on the data that has been obtained. The research results show that applying the problem based learning model can improve student learning outcomes. This is proven by the increase in learning outcomes from cycle I to cycle II. In cycle I the average obtained was 70 with a percentage of complete learning outcomes of 70%. Meanwhile, the learning outcomes for cycle II were an average of 85 with a percentage of complete learning outcomes of 85%. Based on the results of this research, it can be concluded that students' mathematics learning outcomes improve by implementing the problem based learning model for class VII-A students at SMP Negeri 1 Lolomatua for the 2022/2023 academic year.